HUBUNGAN KUALITAS PELAYANAN PERAWATAN SALURAN AKAR GIGI DAN KEPERCAYAAN DENGAN KEPUASAN PASIEN (Tinjauan Literatur) - Selviana Rizky Pramitha; Rahmi Widyanti; Andreyan Rizky Baskara (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
National medical service standards in addition to limiting the autonomy of the medical profession also protect society as a whole. Dental and oral health in Indonesian society is a serious problem and must receive more attention from health workers, both doctors and dental nurses. The government is obliged to ensure the availability of health workers, health service facilities, dental and oral health equipment and medicines in order to provide safe, quality and affordable dental and oral health services to the community, so that it can improve dental and oral health services in preventing dental diseases, treating dental diseases, and restoring dental health which is carried out in an integrated, integrated and sustainable manner and is implemented through individual dental health services, community dental health services and school dental health efforts.